PRENATAL YOGA UNTUK MENGURANGI KETIDAKNYAMANAN KEHAMILAN TRIMESTER 3 - Acholder Tahi Perdoman; Risqi Utami; Fitri Ramadhaniati (Universitas Batam, 2022)
In the process of adaptation to pregnancy, the mother often experiences discomfort. Physical and psychological changes make pregnant women feel tired quickly, have difficulty sleeping, short of breath, legs and arms edema. A study shows the prevalence of low back pain in pregnant women is still high, namely by 24% to 90%. A form of exercise that can help pregnant women feel comfortable during pregnancy or until the delivery process is prenatal yoga. This study aims to determine the effectiveness of prenatal yoga on reducing discomfort during pregnancy. The method used is a qualitative approach with the Literature Review Research method, which is carried out by browsing articles using Google Scholar, Garuda and other electronic media, using the keywords